Mobile Game-Based Learning Application on Science for Indigenous People - Wan Mohd Isa, Wan Abdul Rahim; Hakim Mohamad Hanif, Mohamad Lukman; Mohd Amin, Indah; Ayu Zulkipli, Zulinda (International Journal of Academic Research in Progressive Education and Development, 2023)
This study emphasizes the crucial role of gamification elements in making an application enjoyable and interactive, particularly for indigenous populations. The study identified several issues such as the scarcity of Malay-based educational games available for Indigenous People, which aligned with the Sustainable Development Goals' emphasis on Quality Education. The primary objective of this project is the design and development of the ‘Saintifik’ mobile application, tailored specifically for the public and formatted as a single-user program available on the Android platform with Malay as the primary language. The application's scope is extensive, covering an educational platform that aligned to the syllabus of a Standard 1 Science Curriculum textbook in Malaysia with Malay Language. Designed for individual users, the Saintifik mobile application introduces the Digital Educational Game Life Cycle (DEG) methodology to the study. The application includes several interactive features such as a (i) scoring system, (ii) timer, (iii) gamified challenges and (iv) rewards. The application's significance extends beyond its use as a learning tool for the science curriculum as it also serves as a teaching aid to supplement educational activities. For future improvements, the study recommends the inclusion of more content, additional gamification elements, bilingual support, and compatibility with multiple platforms.